Knowledge attitude and practice of contraception in Barabanki district of Uttar Pradesh: how far are we from meeting the unmet needs of contraception - Thakur, Neha; Khan, Nahid Zia; Rai, Narendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Barabanki one of the most populous districts of Uttar Pradesh with population growth rate being much higher than the national population growth rate. The objective of this study was to gain the knowledge about awareness and contraceptive practices in married women residing in Barabanki. To identify socio-demographic factors associated with unmet needs for contraceptionand also to ascertain the participation of husband in family planning. Methods: A cross sectional study was conducted in outpatient department of Obstetrics Gynecology and Department of Pediatrics in Medical college hospital in Barabanki. 144 females were enrolled in the study during the study period of one year. They were interviewed on the basis of a pre-structured proforma. Data obtained was then analyzed. Results: A total 144 women in the age group 18-45 years participated in the study of which 53% had knowledge of contraception. More than two thirds were not using any form of contraception. The most common method of contraception was barrier method followed by Depot medroxy progesterone acetate. Copper T was least used mode of contraception. The most common source of knowledge regarding contraception was from electronic media followed by friends and family. The most common reason behind the absence of contraception was lack of knowledge of contraception and husband disapproval. Conclusions: Poor knowledge of contraception led to decreased usage of contraceptive measures. Husband participation is virtually absent in family planning leading to high fertility. In order to make our family planning programs successful we must incorporate media for wider coverage to increase awareness and husbands for better implementation.